IL-37 Expression in Patients with Abdominal Aortic Aneurysm and Its Role in the Necroptosis of Vascular Smooth Muscle Cells. (11th May 2022) - Ding, Yan; Wang, Yue; Cai, Yifan; Pan, Chengliang; Yang, Chao; Wang, Miao; Qi, Xiaoyu; Ye, Jing; Ji, Qingwei; Yu, Jian; Xu, Wenbin; Yu, Kunwu; et al.
Abstract : Background . Our previous studies have shown that interleukin- (IL-) 37 plays a protective role in patients and animal models with coronary artery disease. However, the role of IL-37 in patients with abdominal aortic aneurysm (AAA), another artery disease, is yet to be elucidated. Methods and Results . AAA tissues and plasma samples were obtained from patients with or without surgical intervention. Normal renal aortic tissues were collected from kidney transplant donors. Our findings established that in AAA, IL-37 was distributed in endothelial cells, macrophages, and vascular smooth muscle cells (VSMCs) and that it was chiefly concentrated in VSMCs. Furthermore, the expression was found to be downregulated compared with that in normal artery tissues. Immunofluorescence showed that, unlike normal arteries, IL-37 was translocated to the nucleus of VSMCs in AAA. Moreover, in patients with AAA, the expressions of IL-37, IL-6, and tumor necrosis factor- (TNF-) α were increased in the plasma in comparison with the healthy controls. Correlation analysis revealed that IL-37 was positively correlated with IL-6, TNF- α, age, aneurysm diameter, and blood pressure. Furthermore, human aortic vascular smooth muscle cells (HASMCs) were stimulated with angiotensin II (AngII) in vitro to simulate smooth muscle cell (SMC) damage in AAA. A decrease in IL-37 expression and an increase in receptor-interacting serine/threonine-protein kinase 3 (RIPK3) expression were observed in HASMCs stimulated with AngII. On this basis, inhibition of RIPK3 with GSK'872 significantly attenuated necroptosis. Moreover, the necroptosis rates were significantly lowered in HASMCs treated with recombinant IL-37, whereas the rates were enhanced when the cells were depleted of the interleukin. Immunoblotting results showed that both exogenous and endogenous IL-37 could affect the expressions of RIPK3, NLRP3, and IL-1 β . Also, the phosphorylation of RIPK3 and p65 was affected. Meanwhile, IL-37 promoted the transition of SMC from proliferative type to contractile type. Conclusions . The expression of IL-37 in VSMCs decreases in patients with AAA, whereas IL-37 supplementation suppresses RIPK3-mediated necroptosis and promotes the transition of VSMCs from proliferative to contractile type.